Strategi Kultural dan Revitalisasi Tradisi Agama dalam Arus Budaya Konsumen (Studi tentang Tradisi 'Maulidan Jawiyan' di Desa Padurenan, Kecamatan Gebog, Kabupaten Kudus): Cultural Strategy and Revitalization of Religious Tradition in the Flow of Consumer Culture (A Study of the 'Maulidan Jawiyan' Tradition in Padurenan Village, Gebog District, Kudus Regency) - Saifuddin Saifuddin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2010)
Maulidan Jawiyan is the culmination of activities in the tradition of commemorating the birth of the Prophet Muhammad SAW (maulud), which is still preserved today by the people of Padurenan Village, Gebog District, Kudus Regency, Central Java Province. However, a shift in meaning has occurred due to the wave of globalization, which automatically affects the meaning of the ritual itself. This study reveals the cultural strategies adopted by the Padurenan community in facing the flow of consumptive culture. This reality is supported by historical facts that there is an effort to simplify the meaning of the ritual through the process of cultural commodification that occurs in all aspects of life, so the sustainability of the tradition depends on how far the revitalization of meaning is carried out by the community as the sole heir of the tradition. Of course, the aspect of Islamic values becomes important to study as a text that must confront society, which interprets the text in the context of contemporary culture. Maulidan Jawiyan merupakan puncak kegiatan dalam tradisi peringatan hari kelahiran Nabi Muhammad SAW (maulud) yang masih dilestarikan hingga kini oleh masyarakat Desa Padurenan, Kecamatan Gebog, Kabupaten Kudus, Provinsi Jawa Tengah. Namun, pergeseran makna terjadi akibat gelombang globalisasi yang secara otomatis memengaruhi makna ritual itu sendiri. Penelitian ini mengungkap strategi kultural yang diambil oleh masyarakat Padurenan dalam menghadapi arus budaya konsumtif. Realitas ini didukung oleh fakta historis bahwa terdapat upaya untuk mendapatkan kesederhanaan makna ritual melalui proses komodifikasi budaya yang terjadi di segala aspek kehidupan, sehingga keberlangsungan tradisi bergantung pada sejauh mana revitalisasi makna dilakukan oleh masyarakat sebagai pewaris tunggal tradisi tersebut. Tentu saja, aspek nilai-nilai Islam menjadi penting untuk dipelajari sebagai teks yang harus berhadapan dengan masyarakat yang menafsirkan teks tersebut dalam konteks budaya kontemporer.